Politiques d’éclairage public et transformations des espaces urbains : une approche critique - Sandra Mallet (Unité Mixte de Recherche 8504 Géographie-cités, 2017)
This article focuses on the political and social dimensions of urban lighting. It studies the role of public lighting and its importance in urban policy for the transformation of urban spaces. This analysis is based on a study of the urban policy led in Bordeaux over the past two decades. Indeed, the municipality has had an active urban-light policy since the mid-1990s, which has considerably modified its night-time life, landscape and public spaces. The text analyzes the diversity of urban planning tools and the geographical choices made in terms of public lighting, the gap between the geography of urban lighting and the uses of the city during the night, as well as the links between the social composition of spaces in Bordeaux and the lighting policy applied there. It highlights how urban lighting deeply affects the social geography of the city.